The Development of Android-Based Interactive E-Modules in Technical Drawing Subjects - Ovel Geta Nafeli; Rijal Abdullah; Ambiyar; Asrul Huda (Postgraduate, University of Mataram, 2024)
The aim of this research is to produce valid Android- based e-module, practical and effective in the subject of Engineering Drawing. Android- based e-modules are designed to increase student understanding thereby improving student learning outcomes. The data analysis technique used descriptive analysis techniques to describe the validity, practicality, and effectiveness of Android-based e-modules. Results obtained from this development research that the validity of the Android- based e-module is declared valid in the media aspect and material aspect. The practicality of the Android- based e-module from teacher and student responses was stated to be very practical. The effectiveness of Android-based e-modules is stated to be effective in improving learning outcomes. Based on the findings of this research, it was concluded that the Android-based e-module was declared valid with an average value of 0.88. Practicality, it was declared very practical based on teacher responses with an average score of 96.0% and student responses with a score of 87.8%. The effectiveness with classical completeness of 90.91% was declared effective to be used as a learning aid in the Technical Drawing subject.